2004
DOI: 10.1073/pnas.0308308100
|View full text |Cite
|
Sign up to set email alerts
|

Interferon antagonist proteins of influenza and vaccinia viruses are suppressors of RNA silencing

Abstract: Homology-dependent RNA silencing occurs in many eukaryotic cells. We reported recently that nodaviral infection triggers an RNA silencing-based antiviral response (RSAR) in Drosophila, which is capable of a rapid virus clearance in the absence of expression of a virus-encoded suppressor. Here, we present further evidence to show that the Drosophila RSAR is mediated by the RNA interference (RNAi) pathway, as the viral suppressor of RSAR inhibits experimental RNAi initiated by exogenous double-stranded RNA and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
381
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(400 citation statements)
references
References 50 publications
13
381
1
5
Order By: Relevance
“…Recent work has demonstrated a similar antiviral role for RNA silencing in the animal kingdom (Li et al, , 2004. The antiviral response may be triggered by virusspecific dsRNA intermediates produced during genome replication, by transcription from converging promoters, or through recognition of viral RNAs by host RdRP, as proposed in plants (Voinnet et al, 2000;Szittya et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…Recent work has demonstrated a similar antiviral role for RNA silencing in the animal kingdom (Li et al, , 2004. The antiviral response may be triggered by virusspecific dsRNA intermediates produced during genome replication, by transcription from converging promoters, or through recognition of viral RNAs by host RdRP, as proposed in plants (Voinnet et al, 2000;Szittya et al, 2002).…”
Section: Introductionmentioning
confidence: 96%
“…[17][18][19] The apparent absence of RNAi restriction of some viruses could be explained by the counteraction of encoded viral RNA silencing suppressors (RSSs). Several mammalian viruses encode RSSs, 17,[20][21][22][23][24][25][26][27][28][29] although the efficiency of a few of them has been debated. 16,[30][31][32] Proposed RSSs encoded by HIV-1 are the transactivator Tat 20,27 and the Trans Activation Response (TAR) RNA.…”
mentioning
confidence: 99%
“…In particular, mutational analysis of H5N1 NS1 protein indicated that both the RNA-binding and effector domains affect virus pathogenicity synergistically. Our study also demonstrated that expression of H1N1/09 NS1 resulted in enhanced replication of rNDV in human cells, indicating that function of the NS1 proteins can be host-species-specific.Influenza A viruses are associated with significant morbidity and mortality, causing worldwide epidemics yearly and pandemics sporadically (Li et al, 2004). The genome of influenza A virus consists of eight RNA segments that encode nine structural proteins and two non-structural proteins, NS1 and PB1-F2 (Palese & Shaw, 2007).…”
mentioning
confidence: 99%
“…Influenza A viruses are associated with significant morbidity and mortality, causing worldwide epidemics yearly and pandemics sporadically (Li et al, 2004). The genome of influenza A virus consists of eight RNA segments that encode nine structural proteins and two non-structural proteins, NS1 and PB1-F2 (Palese & Shaw, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation